2002
DOI: 10.2320/matertrans.43.42
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Morphology and Si Content on SiO<SUB>2</SUB> Particle Erosion of Full Pearlitic Spheroidal Graphite Cast Iron

Abstract: The effect of morphology and Si content on SiO 2 particle erosion wear of full pearlitic spheroidal graphite cast iron was studied. Experimental data shows the specimens posses more area fraction of cementite for an identical silicon content, that contribute to improve erosion resistance. However, the specimens posses larger interlamellar spacing (λ) at increased Si content, even if the matrix hardness is higher that still debase the erosion resistance. The 2.1Si-air(930 • C) specimens not only possess finer λ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Mechanical properties of pearlitic steels are known to depend strongly on the interlamellar spacing of pearlite. [16][17][18] Various heat treatment processes have been applied to obtain desirable pearlite interlamellar spacing and mechanical strength of steels. In this research, an attempt was made to obtain the quantitative correlations among microstructure, strength and magnetic properties of variously heat treated eutectoid steel.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical properties of pearlitic steels are known to depend strongly on the interlamellar spacing of pearlite. [16][17][18] Various heat treatment processes have been applied to obtain desirable pearlite interlamellar spacing and mechanical strength of steels. In this research, an attempt was made to obtain the quantitative correlations among microstructure, strength and magnetic properties of variously heat treated eutectoid steel.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers [2][3][4][5][6][7][8][9][10][11][12][13][14] have discussed erosion mechanisms for some metallic materials. They utilized mechanics analysis to get results, which are summarized as follows: cutting erosion occurs at a low incident angle and deformation erosion occurs at a high incident angle.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the peak angle of the erosion rate curve did not shift or vary with the volume fraction of pearlite. However, other studies [11][12][13] revealed that when the full ferrite matrix is transformed into pearlite, the peak angle of the erosion rate curve shifts to a higher angle. The above results indicated that the change in the peak erosion rate due to changes in the lamellae cementite needed to be explored for PDI.…”
Section: Introductionmentioning
confidence: 93%